From Hopeless to Curious? Thoughts on Hausman's "Dubious to Hopeless" Critique of Contingent Valuation. (22nd October 2013) - Haab, Timothy C.; Interis, Matthew G.; Petrolia, Daniel R.; Whitehead, John C.
Abstract: Hausman "selectively" reviewed the contingent valuation method (CVM) literature in 2012 and failed to find progress in the method during the 18 years since Diamond and Hausman argued that unquantified benefits and costs are preferred to those quantified by CVM. In this manuscript, we provide counter‐arguments to Hausman's claims, not with the intent to convince the reader that the debate over CVM is settled in favor of the method, but rather to argue that the intellectual debate over CVM is ongoing, that dismissing CVM is unwarranted, and that plenty of work remains to be done for the truly curious researcher.